Evolution Solutions of Perturbed Khokhlov-Zabolotskaya Equation (Journal of Partial Differential Equations, 2018)
This paper is concerned with the exact solutions of Khokhlov-Zabolotskaya (KZ) equation with general perturbation. With the help of appropriate transformations and assumptions, the wave theory of Hopf equation is applied to get partial exact solutions. In addition, some examples and numerical simulations are presented to illustrate our analytical results.